Oficina de Tesorería. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 1990)
Tatiana Matamoros, Magaly Moya, Osvaldo Solano, Eduardo Alexander, Martha Araya, Alban Espinoza, Enid Guzmán, Cristina Pereira (Jefa), Sandra Villalobos.
Colección Fototeca UNED
Keywords: Matamoros Sánchez, Tatiana; Moya Lacayo, Magaly; Solano Peralta, Osvaldo; Alexander, Eduardo; Araya Serrano, Martha; Espinoza Ortiz, Alban Roberto; Guzmán Cabezas, Enid; Pereira Gamboa, Ana Cristina; Villalobos Barquero, Sandra; UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA